RIGHT-WING FRENCH MEDIA COVERAGE OF THE RASSEMBLEMENT NATIONAL’S 2027 PRESIDENTIAL CANDIDATES - Sundari, Amelinda; Laksman-Huntley, Myrna (International Review of Humanities Studies, 2026)
The 2027 French presidential election has become a contest over political legitimacy, and the media play a key role in shaping candidates’ images. Within the right-wing camp, Rassemblement National (RN) presents two potential figures, Marine Le Pen and Jordan Bardella. Le Pen faces legal threats that could prevent her candidacy, while Bardella is projected as a successor to represent RN in the contest. Drawing on framing theory Pan & Kosicki (1993) and Critical Discourse Analysis Fairclough (1995), this qualitative study investigates right-wing French media preferences between these two candidates. The analysis examines three articles each from Le Figaro and Le Point. Framing analysis finds that Le Figaro places Le Pen at the center through syntactic framing that reinforces her legitimacy. By contrast, Le Point foregrounds Bardella’s readiness and leadership capacity through marked rhetorical structures. CDA corroborates these results by revealing divergent editorial focuses. At the macro level, Le Figaro projects a populist image by positioning Le Pen as RN’s emblematic opposition to the government, whereas Le Point exemplifies RN’s de-demonization by giving Bardella space to craft a more moderate, broadly acceptable party image. These findings offer practical guidance for politicians seeking targeted media engagement.